2005
DOI: 10.1080/18811248.2004.9726437
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gamma-Ray Dose Components in Criticality Accident Situations

Abstract: Component analysis of gamma-ray doses in criticality accident situations is indispensable for further understanding on emission behavior of gamma-rays and accurate evaluation of external exposure to human bodies. Such dose components were evaluated, categorizing gamma-rays into four components: prompt, delayed, pseudo components in the period of criticality, and a residual component in the period after the termination of criticality. This evaluation was performed by the combination of dosimetry experiments at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The uncertainty of 10-20% is allowable in radiation emergency medicine: its criterion is roughly 50% in 48 hrs and 25% in a week after the accident. 11) After the thorough investigation of the accident, the Monte Carlo simulation 10,12) under the condition at the time of the accident can remove the uncertainty from the first estimation.…”
Section: Dosimetry Using Area Dosimetersmentioning
confidence: 99%
See 4 more Smart Citations
“…The uncertainty of 10-20% is allowable in radiation emergency medicine: its criterion is roughly 50% in 48 hrs and 25% in a week after the accident. 11) After the thorough investigation of the accident, the Monte Carlo simulation 10,12) under the condition at the time of the accident can remove the uncertainty from the first estimation.…”
Section: Dosimetry Using Area Dosimetersmentioning
confidence: 99%
“…As regards the dose range in criticality accidents, the previous criticality accident dosimetry at TRACY showed that the dose measured within a radius of $5 m from the radiation source was approximately in the range of 10 À15 -10 À17 Gy/fission. 9,10) The number of fissions was reported to be in the range of 10 15 -10 20 in the past sixty criticality accidents.…”
Section: Dosimetry Using Area Dosimetersmentioning
confidence: 99%
See 3 more Smart Citations